Do overly complex reporting guidelines remove the focus from good clinical trials?. (16th August 2021) - Howick, Jeremy; Webster, Rebecca; Knottnerus, J André; Moher, David
Abstract : The ever increasing emphasis on complex reporting guidelines is getting in the way of designing and conducting good clinical trials, say Jeremy Howick, Rebecca Webster, and J André Knottnerus . But David Moher argues that, while following the guidelines can be frustrating, such complexity remains necessary and is improving research, not impeding it